3D Modelling of Geoelectrical Resistivity Data to Determine the Direction of Landslides in Kastoba Lake, Bawean Island, Indonesia - Karimah Karimah; Adi Susilo; Eko Andi Suryo; Aunur Rofiq; Muhammad F.R. Hasan (Postgraduate, University of Mataram, 2022)
Landslides are one of the factors caused by subsurface structures that are not compact, and have low density or resistivity values due to changes in groundwater. Rainwater that infiltrates into the ground will reach to an impermeable layer which is identified as a slip plane. This research was conducted in the Kastoba Lake area, Bawean Island, Indonesia. The purpose of this study is to determine the slip plane and the direction of the landslide in the studied area. Data acquisition was carried out based on a preliminary study of residual anomaly contour analysis from gravity data, then geoelectric data acquisition was carried out in the studied area. The results of lithological analysis on 3D geoelectric resistivity modeling in this study obtained three layers of subsurface structures, namely topsoil, clay, and lavas. The slip plane of the study area is above the clay layer (7.25 meters depth). The results of the 3D interpretation indicated that the direction of the landslide was towards the north, as evidenced by the existence of public information that the area studied had landslides with the avalanche direction towards the north.Â For further analysis, a factor of safety analysis is needed based on the analysis of the bore hole drilling method in the studied area